Geochemical and thermodynamic controls in the formation of mineral assemblages from the metamorphic aureole of the Bushveld Complex in the Potgietersrus area - Sharpe, M.R. (University of Pretoria, 2021)
Dissertation (MSc)--University of Pretoria, 1984.